2015
DOI: 10.1088/0004-637x/808/1/92
|View full text |Cite
|
Sign up to set email alerts
|

Optical Detection of the Pictor a Jet and Tidal Tail: Evidence Against an Ic/CMB Jet

Abstract: New images of the FR II radio galaxy Pictor A from the Hubble Space Telescope reveal a previously undiscovered tidal tail, as well as a number of jet knots coinciding with a known X-ray and radio jet. The tidal tail is approximately 5″ wide (3 kpc projected), starting 18″ (12 kpc) from the center of Pictor A, and extends more than 90″ (60 kpc). The knots are part of a jet observed to be about 4′ (160 kpc) long, extending to a bright hotspot. These images are the first optical detections of this jet, and by ext… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 24 publications
(42 reference statements)
1
16
0
Order By: Relevance
“…However, strong jet-medium interaction on larger scales cannot be ruled out from our observations. Indeed, jet stratification possibly arising due to strong jet-medium interaction has been suggested for the X-ray jet of Pictor A by Hardcastle et al (2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, strong jet-medium interaction on larger scales cannot be ruled out from our observations. Indeed, jet stratification possibly arising due to strong jet-medium interaction has been suggested for the X-ray jet of Pictor A by Hardcastle et al (2015).…”
Section: Discussionmentioning
confidence: 99%
“…Inskip et al (2010), using near-IR data, concluded that Pictor A's surface brightness distribution is best modelled by a disky galaxy profile with a nuclear point source. A tidal tail was recently discovered by Gentry et al (2015), starting 18 ′′ (12 kpc) north of Pictor A, sweeping to the west along a path about 60 kpc long. This long tail indicates the occurrence of a merger event some hundred million years ago.…”
Section: Introductionmentioning
confidence: 99%
“…While some other jets are comparably long, no other known jet boasts the same combination of length, number of visible components and low redshift that 3C 111 does. For example, the jet of Pic A (Marshall et al 2010;Gentry et al 2015;Hardcastle et al 2016), which is similarly straight, longer in angular extent (almost 4'), and is about 30% nearer, has only three components that have been detected in the near-IR, while the jet of 3C 273 (Jester et al 2006), which extends for a somewhat greater distance from its host galaxy and is somewhat brighter, is nearly 4× as far at a redshift z = 0.158. The analysis discussed in this paper strongly disfavors the EC/CMB model as the dominant X-ray emission mechanism in several of the components of 3C 111's jet.…”
Section: Discussionmentioning
confidence: 99%
“…Hubble Space Telescope (HST) observations of the jet were taken as part of this project, but are not described here: see Gentry et al (2015) for details of the observations and their results. We comment on the implications of these observations for models of the jet in the discussion.…”
Section: Other Datamentioning
confidence: 99%